Islam–Science Integration in Indonesian Integrated Islamic Junior High Schools - Sulastri, Sulastri; Anwar, Abu (International Journal of Multidisciplinary Research of Higher Education, 2026)
The integration of Islam and science in education represents a strategic effort to develop holistic learning within integrated Islamic schools in Indonesia. This study explores how Islam–science integration is implemented in Integrated Islamic Junior High Schools, focusing on curriculum design, pedagogical practices, and the internalization of tauhid values. Using a qualitative field study approach, data were collected through classroom observations, in-depth interviews with principals and teachers, and document analysis. Findings indicate that integration is achieved by linking scientific concepts with Qur’anic verses (ayat kauniyah), embedding daily worship practices, strengthening moral character, and positioning teachers as murabbi who nurture intellectual and spiritual growth simultaneously. The model enhances students’ scientific literacy, spiritual awareness, and balanced character formation, though challenges remain in teachers’ pedagogical competence and limited instructional time. Overall, the study demonstrates that Islam–science integration fosters students who are balanced in faith, knowledge, and ethics, while offering a practical framework for curriculum innovation in Islamic education. These findings contribute to the global discourse on religion–science integration and provide insights for policymakers and educators seeking to advance integrative approaches in contemporary schooling.